Wildfire particulate matter in Shasta County, California and respiratory and circulatory disease-related emergency department visits and mortality, 2013–2018. Issue 1 (21st February 2021) - Casey, Joan A.; Kioumourtzoglou, Marianthi-Anna; Elser, Holly; Walker, Daniel; Taylor, Stephanie; Adams, Sarah; Aguilera, Rosana; Benmarhnia, Tarik; Catalano, Ralph
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Wildfire smoke harms health. We add to this literature by evaluating the health effects of California's 2018 Carr Fire and preceding wildfire seasons in Shasta County. Methods: With data from the Shasta County Health and Human Services Agency, we examined the link between weekly wildfire fine particulate matter (PM2.5 ) exposure estimated using a spatiotemporal multiple imputation approach and emergency department (ED) visits and mortality using time-series models that controlled for temporal trends and temperature. Results: Between 2013 and 2018, Shasta County experienced 19 weeks with average wildfire PM2.5 ≥5.5 μg/m 3 (hereafter, "high wildfire PM2.5 concentration"). Among all Shasta County Zip Code Tabulation Areas (ZCTAs; n = 36), we detected no association between high wildfire PM2.5 concentrations and respiratory or circulatory disease-related ED visits or mortality. Subsequent analyses were confined to valley ZCTAs (n = 11, lower elevation, majority of population, worse air quality in general). In valley ZCTAs, high wildfire PM2.5 was associated with a 14.6% (95% confidence interval [CI] = 4.2, 24.9) increase in same-week respiratory disease-related ED visits but no increase in the subsequent 2 weeks nor on circulatory disease-related mortality or ED visits or all-cause mortality. Two weeks after high wildfire PM2.5 weeks, respiratory disease-related deaths decreased (–31.5%, 95% CI = –64.4, 1.5). The 2018 Carr Fire appeared to increase respiratory disease-related ED visits by 27.0% (95% CI = 4.0, 50.0) over expectation and possibly reduce circulatory disease-related deaths (–18.2%, 95% CI = –39.4, 2.9). Conclusions: As climate change fuels wildfire seasons, studies must continue to evaluate their health effects, particularly in highly exposed populations.